ФОРМУВАННЯ ПРАКТИЧНИХ НАВИЧОК ПРИ ВИКОНАННІ ПРОГРАМНИХ ЗАВДАНЬ ДИСЦИПЛІНИ “ОСНОВИ ЗОВНІШНЬОЇ РЕКЛАМИ” (Педагогіка вищої та середньої школи, 2006)
In article is considered the questions of forming of practical experience in the execution of programme tasks of discipline “Principles of external advertisement" in preparing of teacher Fine Art.